A transnasal foreign body penetrating the spinal cord from the nasopharynx. Issue 5 (October 2020) - Takagi, Daiki; Shinohara, Naoki; Nishida, Naoya; Matsui, Seishi
Abstract: Objective and importance: This is the first article regarding a transnasal Foreign bodies (FB) penetrating the spinal cord. We tried to remove it safely with a bilateral approach by performing a nasal endoscopy and partial laminectomy. Clinical presentation: During logging work, a tree hit the occipital region of a 47-year-old man, producing unconsciousness with left paresis. Although he did not remember his injuries due to traumatic amnesia, a computed tomography (CT) scan showed a metal rod lodged from the left side wall of the nasopharynx to the spinal column at the cranial–cervical transition. Intervention: A C1 laminectomy, partial occipital bone resection, and endoscopic intranasal extirpation were done jointly by an otolaryngologist and neurosurgeon under general anesthesia to safely remove the FB. All procedures were performed in the right lateral decubitus position so we could approach both the nasopharynx and occipital sides. The otolaryngologist withdrew the FB from the nasal cavity using an endoscope while the neurosurgeon monitored the occipital bone side. The FB was safely removed. Conclusion: The site of penetration at the nasopharynx contracted gradually to a scar with no cerebrospinal fluid (CSF) leak. The patient was finally discharged 39 days after surgery with no motor/sensory paralysis.